Study of shear-plastic slip mechanism based on TC4 titanium alloy - Bo Hu; Zichuan Zou; Pengfei Tian; Nian Xiao; Sen Yuan; Xianfeng Zhao (PLoS ONE, 2026)
The stagnation point and dead metal zone in the cutting process directly or indirectly affect the chip formation and stress distribution, while the stress distribution in the machining process determines the plastic slip direction of the material. Aiming at the current insufficient research on the dead metal zone and stagnation point theory, this paper divides the cutting process into rounded edge contact stage and rounded edge-rake face contact, constructs a slip line field model with dead metal zone based on the stress distribution and pressure distribution of the two stages, calculates the slip line field through the Cauchy problem, and plots the slip line field through the secondary development port in SOLIDWORKS. The dead metal zone model is based on the stress distribution of the obtuse circular contact, and the stagnation point occurs at the critical condition of the elastic-plastic transition of the material, i.e., at the maximum shear stress of the process. The dead metal zone and stagnation point are examined based on simulation, and the slip line field model is verified experimentally. The results show that the dead metal zone model can be predicted more accurately when the tool rake angle is 15° or less, and the greatest influence on the stagnation point is the tool rake angle and the radius of the rounded edge of the tooltip, and the slip line field model containing the dead metal zone can more accurately reflect the plastic slip of the real cutting process. It can be seen that the dead metal zone model, stagnation point model, and slip line field model illustrate the cutting mechanism of the elastic and plastic phases of the cutting process, which lays a research foundation for the subsequent study of tool wear, chip formation, and machining surface quality.